Prognosis after one- and two-stage revision surgery for periprosthetic joint infection: A systematic review and meta-analysis - Yiyuan Sun; Menghao Liu; Dan Xiao; Qi Li; Huan Xiong; Xue Luo; Boyu Zhu; Weili Fu (Journal of Orthopaedic Surgery)
Objective Revision surgeries for periprosthetic joint infections (PJIs) in arthroplasty can follow either one- or two-stage treatment protocols. Previous studies have reported similar reinfection rates and reductions in complication rates for both treatment options. However, the literature on the selection of one protocol is still controversial. Thus, our aim was to compare the outcomes, including reinfections, complications, reoperations, and mortality, associated with one- and two-stage revision surgeries for PJI via a systematic review and meta-analysis of comparative studies. Methods Comparative studies were identified through searches in PubMed, EMBASE, the Web of Science, and the Cochrane Library as of November 2023. RevMan version 5.3 was used for the analyses. The included studies directly compared one-stage revisions with two-stage revisions for PJI. The primary outcomes included reinfection, complications, reoperation, and mortality. Results Sixteen cohort studies (fifteen retrospective and one prospective) were included in the systematic review. All studies comprising 2039 patients were included in the meta-analysis. Fourteen studies reported reinfection patient risk postrevision; when pooled via random effects models, 10.02% of patients in the one-stage group and 14.75% of patients in the two-stage group were reinfected, indicating low heterogeneity (risk ratio = 0.69; 95% CI = 0.50 – 0.94, I 2 = 0%). A pooled analysis of ten studies reported complications between the two groups. Compared with the two-stage group, the one-stage group was associated with significantly fewer complications (risk ratio = 0.76; 95% CI = 0.63 – 0.91, I 2 = 27%). The meta-analysis revealed no significant difference in reoperation events between the 1st-stage and 2nd-stage groups in nine studies (risk ratio = 0.77; 95% CI = 0.59 – 1.01, I 2 = 20%) or in mortality in ten studies (risk ratio = 0.93; 95% CI = 0.49 – 1.78, I 2 = 0%). Conclusions Among the available observational studies, the meta-analysis revealed a lower incidence of reinfection and complications in the one-stage group than in the two-stage group, but there were no significant differences in reoperation events or mortalities.